Analisis Throughput Distribusi Jaringan Nirkabel Pada Politeknik Bumi Akpelni - Wardana, M. Rifki; Santoso, Dwi Budi (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2023)
Wireless networks, also known as wireless or Wi-Fi networks, are networks where users of electronic devices can connect and communicate with each other without using physical cables or wired connections. One of the factors that supports the capabilities of wireless networks is throughput. In the analysis of wireless network throughput, researchers conducted a study at Politeknik Bumi Akpelni, a maritime college. The research was conducted using computer simulations or field testing to examine factors that affect throughput, such as bandwidth, latency, and user density. The testing was performed by evaluating the wireless network transmitted by an access point device with the IEEE 802.11 ac standard, which operates at two frequencies: 2.4 GHz and 5 GHz. The testing was divided into three stages: testing wireless network throughput with obstacles (walls), testing wireless network throughput without obstacles, and testing wireless network throughput based on user density. The test results were categorized as very good, but it should be noted that the amount of bandwidth affected the quality of the throughput obtained. The more users there are, the smaller the throughput obtained.